Peran Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran melalui Pengembangan Guru di SDN Menyiuh - Amir Amir (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Effective language teaching in secondary schools requires more than just grammatical proficiency; it necessitates an understanding of sociocultural and pragmatic aspects of communication. This paper aims to examine how the school principal's leadership plays a pivotal role in enhancing the quality of instruction through teacher development, with a specific focus on the integration of sociolinguistic approaches in language teaching. This study employs a qualitative descriptive method using a literature review approach. Data were gathered through extensive searches and analyses of academic documents journal articles, books, and conference proceedings from reputable databases like Google Scholar. Thematic content analysis was used to identify key patterns, concepts, and findings. The implementation of sociolinguistic-based strategies such as discourse analysis, role-play simulations, and discussions on language variation has shown positive outcomes in enhancing students’ understanding of language register, politeness norms, and context-sensitive language use. These practices also foster students’ pragmatic and sociocultural competence, bridging linguistic knowledge with real-world communication. The study underscores the role of sociolinguistics in fostering communicative competence and highlights the principal's role in facilitating such innovations through strategic teacher empowerment and professional development initiatives.